The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1371/journal.pone.0213225
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and enablers for practicing kangaroo mother care (KMC) in rural Sindh, Pakistan

Abstract: Background More than 2.5 million newborns die each year, accounting for 47% of children dying worldwide before their age of five years. Complications of preterm birth are the leading cause of death among newborns. Pakistan is amongst the top ten countries with highest preterm birth rate per 1000 live births. Globally, Every Newborn Action Plan (ENAP) has emphasized on Kangaroo Mother Care (KMC) as an essential component of neonatal health initiatives. Materials and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 26 publications
(34 reference statements)
2
23
0
3
Order By: Relevance
“…Not only are husbands and mothers-in-law important household decision-makers that influence the uptake of KMC [ 6 , 11 , 12 ], they are also the backbone of her support network. While KMC is recommended as a feasible and cost-effective intervention for resource-limited settings in comparison with conventional incubator care, this research highlights that the burden of care may be shifted onto mothers and her family to fill the gap created by a lack of human resource [ 24 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not only are husbands and mothers-in-law important household decision-makers that influence the uptake of KMC [ 6 , 11 , 12 ], they are also the backbone of her support network. While KMC is recommended as a feasible and cost-effective intervention for resource-limited settings in comparison with conventional incubator care, this research highlights that the burden of care may be shifted onto mothers and her family to fill the gap created by a lack of human resource [ 24 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 22 included studies reported on factors influencing and barriers to KMC utilisation amongst PLBWIs mostly published between 2012 and August 2020. The included studies comprised four cross-section studies 36 , 37 , 38 , 39 three randomised control trial studies, 40 , 41 , 42 one explorative study 43 seven descriptive studies, 44 , 45 , 46 , 47 , 48 , 49 , 50 one longitudinal study, 49 one qualitative study, 51 two dissertations 39 , 52 and two formative study. 47 , 53 Almost 10 studies were based on face-to-face interviews, 36 , 37 , 38 , 43 , 44 , 45 , 46 , 47 , 48 , 50 of which seven were qualitative study interviews, 36 , 37 , 43 , 47 , 48 , 50 , 53 three were mixed-method studies 38 , 44 , 46 and nine were quantitative studies.…”
Section: Resultsmentioning
confidence: 99%
“…21 In this perspective, a study carried out in Pakistan showed that the support offered by the health professionals to the motherchild binomial was considered a primary factor to ensure KM home follow-up. 22 Regarding this continuity of care, a research study carried out in the province of Quebec pointed out the liaison nurses as being fundamental so that the levels of health care may come to operate as a network, in an articulated and coherent manner. This is possible because the nurses develop actions focused on the needs of the patient and in conjunction with the extra-hospital services, ensuring continuity of care for the patients after hospital discharge.…”
Section: Discussionmentioning
confidence: 99%